MANAJEMEN BERBASIS SEKOLAH: STRATEGI ALTERNATIF DALAM PERSAINGAN MUTU - Busthomi Ibrohim (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
Politically, School Based Management (SBM) becomes the mouthpiece of all issues in the field of education that will be portrayed in schools, because the school is the last network of educational bureaucracy. SBM is also a form of operationalization of the decentralization or education autonomy policy in relation to regional autonomy. Theoretically, SBM is also a concept that offers autonomy to schools in order to improve quality, efficiency and equity of education in order to accommodate the interests of local communities as well as establishing close cooperation between schools, communities and governments. Operationally SBM is an idea that places the authority of school management in a system entity. Based on the above view, this article outlines the basic framework of SBM as a strategy for improving the quality of education. With SBM, principals, teachers and learners get the opportunity to innovate and improvise in schools related to curriculum, learning, managerial and others. So the principal serves as an educator, manager, administrator, supervisor, leader, innovator, motivator, figure, and mediator. SBM also calls for the creation of new institutional arrangements and institutions, including: the establishment of school boards, development of school strategy planning, develop of annual school planning, internal monitoring and self-assessment, annual reporting, school opinion surveys of school stakeholders. Keywords. School Based Management, Decentralization of Education, Quality Assurance, Autonomy of Education, School Committee